Developmental transition of visual and nonvisual photoreception and circadian clock during smoltification in the eye and brain of Atlantic salmon - Mariann Eilertsen; David W. P. Dolan; Rita Karlsen; Tom Ole Nilsen; Wayne I. L. Davies; Jon Vidar Helvik (PLoS ONE, 2026)
Seasonal variation in photoperiod is an important cue that regulates changes in physiology and behavior during the anadromous lifestyle of Atlantic salmon. The parr-smolt transformation or smoltification, where fish migrate from rivers to the ocean, is promoted by an increased photoperiod in the spring. Photoperiodic information is transferred through the light-brain-pituitary axis, resulting in pituitary hormones stimulating changes related to this transition. The light environment is perceived by ocular photopigments in the rods and cones that convey image formation and via nonvisual photoreceptors entraining biological processes that synchronize with circadian and circannual light rhythms through the molecular clock mechanism. In this study, the dynamic expression of visual and nonvisual opsin genes and clock genes through smoltification were revealed by RNA sequencing. The results showed a dramatic transition of the teleost visual system by changes in expression of the tandem duplicated medium-wavelength-sensitive ( mws or “green”) and long-wavelength-sensitive ( lws or “red”) opsin genes during seawater migration, shifting the spectral sensitivity of the green opsins by up to 40 nm towards shorter wavelengths. Concomitantly, the expression of the lws opsin gene that forms a photopigment with the most extreme absorbance maximum was upregulated. Among the nonvisual opsins, the pineal-specific exorhodopsin was greatly upregulated in seawater, coinciding with an increased expression of important enzymes that dictate melatonin synthesis. Analyzing the components of the salmonid molecular clock expressed during smoltification showed that clock genes were dynamically expressed with changes in expression both related to changes in the photoperiod and the developmental transition from freshwater to seawater. The transcriptomic profile of the teleost brain through smoltification was shown to coincide with important genes that underpin the mammalian model of photoperiodism that drive summer and winter physiology, supporting common photoperiodic pathways that regulate seasonality in vertebrates.